THE EFFECT OF “APSA AMINOVIT” DIETARY FEED SUPPLEMENT ON BLOOD INDICES UNDER QUAIL EIMERIOSIS - Rudik, O. V. (Scientific Progress & Innovations, 2020)
The results of scientific and economic studies show that the quails affected by eimeriosis had clinical signs of watery feces, state of oppression, they did not take food, their wing tips were dirty and in the process of treatment it has been established that watery feces ceased on the 3rd, 4th day. The state of quails oppression was registered from the moment of infestation to the 6th day. Coprological examinations have established that E. tenella – 1.3 thousand and E. necatrix – 1.5 thousand eimeria oocysts per 1g of feces were registered in the quails kept in “Iris-2009” LLC, and prevalence of infection made 100 %. On the 14th day after “Diacox 0.2 %” treatment ЕЕ and ІЕ made 100 % and blood indices achieved their physiological parameters again. The first experimental group received “Diacox” in combination with compound poultry feed during 5 days in a dose of 1 mg per 1 kg of a compound poultry feed. An increase in the amount of erythrocytes by 21.5 % (Р<0.05) was registered in morphological indices, and there were no visible changes after treatment in such indices like leukocytes, eosinophiles, pseudo-eosinophils and monocytes. As a result of studies experiment it has been registered an insignificant decrease in the amount of basophils by 32.4% (Р<0.01), and the amount of leukocytes from by 3.8 % (Р<0.05); quails biochemical indices showed an increase in the amount of hemoglobin by 13.7 % (Р<0.001), total protein by 16.6 % (Р<0.001), creatinine by 9.2 % (Р<0.05), AST activity increased by 9.3 % (Р<0.05) the amount of phosphorus decreased by 63.7 % (Р<0.01), potassium by 4.1 % (Р<0.05), uric acid by 54.6 % (Р<0.01) as compared with the period before quails treatment. The second experimental group received “Diacox 0.2%” with compound poultry feed at a dose of 1mg per 1 kg of a compound poultry feed in combination with “ Aрsa aminovit” dietary feed supplement at a dose of 1ml per 1l of water during 5 days. Some changes have been registered in morphological indices after quails treatment: the amount of erythrocytes increased by 17.6% (Р<0.001), pseudo-eusinophiles by 22.7 % (Р<0.001), and the amount of leukocytes decreased by 24.9 % (Р<0.01), basophils by 47.9 % (Р<0.01), eosinophiles by 15.6 % (Р<0,01), lymphocytes by 5.2 % (Р<0.05), monocytes by 8.4 % (Р<0.05); some changes in biochemical indices were registered as well: hemoglobin increased by 21.9 %, (Р<0.001), total protein by 6 %, (Р<0,05), creatinine by 4.2 %, (Р<0.05), phosphorus content increased by 50.3 %, (Р<0.01), potassium by 44.9 %,(Р<0.01), uric acid by 47.0 %, (Р<0.01), AST activity increased by 3.74 %, (Р<0.05).